Soft values of nature meeting mental needs of wellbeing and profitability gives incentives for improvement planning supporting most sustainability goals - Skärbäck, Erik; Filén, Elias; Orban, Kristina (American Journal of Social Sciences and Humanities, 2026)
Soft natural values are often neglected in planning. One approach has been to aim for a balance of natural resources. However, balancing is no longer sufficient, as global consumption continues to deplete resources, reduce biodiversity, and drive severe climate crises. Instead, every project must actively contribute to improvements. But how can we expect property owners to deliver environmental qualities that exceed previous standards? Achieving this requires economic incentives—a win-win for all stakeholders, from developers to tenants, employees, municipalities, and even nations. Our approach summarizes research findings from the past half-decade on how natural qualities meet fundamental human needs for mental well-being and health. Two resources have been particularly valuable: the Alnarp Rehabilitation Garden and a large Public Health Survey of the Scania Region in southern Sweden, which enabled validation of eight specific sensory dimensions. One key finding is that university productivity is significantly associated with tree cover near campus buildings and with the density of sensory dimensions across an entire campus. These scientific insights led to the development of an assessment protocol for restorative workplaces. A group of property owners and tenant companies formed a mutual partnership for a testbed of an evaluation protocol. Practical implications now show that the tool effectively supports improvements. When stakeholders and staff discuss evaluation questions together, they gain a deeper understanding of how specific characteristics meet specific needs. Achieving social, ecological, and economic goals while improving one’s workplace proves highly motivating for all involved.